(untitled) (Per Musi, 2015)
In a philosophical approach to the work of North-American composer John Cage, we use Derridean’s notions of ghost and spectrum for understanding his conception of sound and revealing the political status of his art. This condition is absolutely linked to a desire for justice that emerges in the roots of an America devastated by European dominance. Its manifestation in Cage’s work is the intervention and the disarmament of Western music. Thus, artwork for John Cage is always rooted in a political work which horizon is justice. A horizon that Jacques Derrida puts as a basic condition for all doing.